PENGARUH LOAN TO DEPOSIT RATIO, LOAN TO ASSET RATIO, CAPITAL ADEQUACY RATIO DAN KUALITAS AKTIVA PRODUKTIF TERHADAP PROFITABILITAS PADA PT BANK PEMBANGUNAN DAERAH BALI KANTOR PUSAT DENPASAR - Miadalyni, Desi; Dewi, Sayu Kt Sutrisna (E-Jurnal Manajemen, 2013)
ABSTRACT Resulted in the rapid development of banking stiff competition among fellow banks or other financial institutions. Therefore, the banking industry is required to have a business that is economical, effective, and efficient. One of the elements that are all concerned to know whether an efficient and banking institutions can be seen from the level of health, where its application can be seen on the profitability of each bank. This study examined the effect of variable loan-to-deposit ratio (LDR), loan-to-asset ratio (LAR), capital adequacy ratio (CAR), and the quality of earning assets (KAP) simultaneously and partially on profitability. This research was conducted at PT. Regional Development Bank Headquarters Denpasar Bali 2007-2011. Observations made ?? in the next 5 years so getting 60 observations. To solve the problem used multiple linear regression using SPSS 17.0 for Windows. F test results indicate that the loan-to-deposit ratio, loan-to-asset ratio, capital adequacy ratio, asset quality and simultaneously significant effect on profitability in PT Bank Pembangunan Daerah Bali Denpasar Headquarters. T-test results showed that the loan-to-deposit ratio and a significant positive effect on profitability, loan to assets, capital adequacy ratio and asset quality and significant negative effect on profitability. Key: LDR, LAR, CAR, KAP effect on profitability.
Keywords: LDR; LAR; CAR; KAP effect on profitability